Association of sputum microbiome with clinical outcome of initial antibiotic treatment in hospitalized patients with acute exacerbations of COPD. (October 2020) - Liu, Haiyue; Zheng, Daowen; Lin, Yanxia; Liu, Zuheng; Liang, Zhenyu; Su, Jin; Chen, Rongchang; Zhou, Hongwei; Wang, Zhang
Graphical abstract: Abstract: Identification of risk factors for antibiotic treatment failure is urgently needed in acute exacerbations of chronic obstructive pulmonary disease (AECOPD). Here we investigated the relationship between sputum microbiome and clinical outcome of choice of initial antibiotics during hospitalization of AECOPD patients. Sputum samples of 41 AECOPD patients and 26 healthy controls were collected from Guangzhou Medical University, China. Samples were processed for 16S rRNA gene-based microbiome profiling. Thirty patients recovered with initial antibiotic treatment (antibiotic success or AS), while 11 patients showed poor outcome (antibiotic failure or AF). Substantial differences in microbiome were observed in AF versus AS patients and healthy controls. There was significantly decreased alpha diversity and increased relative abundances of Pseudomonas, Achromobacter, Stenotrophomonas and Ralstonia in AF patients. Conversely, Prevotella, Peptostreptococcus, Leptotrichia and Selenomonas were depleted. The prevalence of Selenomonas was markedly reduced in AF versus AS patients (9.1 % versus 60.0 %, P = 0.004). The AF patients with similar microbiome profiles in general responded well to the same new antibiotics in the adjusted therapy, indicating sputum microbiome may help guide the adjustment of antibiotics. Random forest analysis identified five microbiome operational taxonomic units together with C-reactive protein, procalcitonin and blood neutrophil count showing best predictability for antibiotic treatment outcome (area under curve 0.885). Functional inference revealed an enrichment of microbial genes in xenobiotic metabolism and antimicrobial resistance in AF patients, whereas genes in DNA repair and amino acid metabolism were depleted. Sputum microbiome may determine the clinical outcome of initial antibiotic treatment and be considered in the risk management of antibiotics in AECOPD.